Digital stereo close range videogrammetry for high accuracy 3D measurement motion tracking system - Ibrahim, Mohd. Sharuddin; Setan, Halim (2007)
With enhances technology of digital imaging and video resolution up to 1080dpi, research has shown that sequence image from a frame of images can be used to provide high accuracy measurement. Usually photogrammetrist used still image for measurement and modelling of object. Videogrammetry refers to video images taken using camcorder or movie function on digital still camera. Video movie consists of sequences of images (or frames). If video speed is 25 fps (frame per second) and taken for 1 minute (i.e. 60 seconds), there are 25 frame per second or overall 1500 image. Real time video capturing, image processing, image analysis, motion detection, motion tracking, bundle adjustment, 3D coordinates on each movement and draw a patent of motion are possible. This paper focuses on the on-going study to develop a real time high accuracy motion tracking system. It highlights the capabilities of video as a tool for 3D measurement and modelling, as well as still image. Several advantages are discusses in detail. The development also focuses on the optimization, in terms of method, procedure, low-cost and accurate results. The research methodology consists of real time video capturing, image analysis, bundle adjustment, motion detection, motion tracking and 3D coordinate movement on each frame. With this development, it can be applied to measure moving object such as sport analysis, metrology, inspection, and model the motion of human for medical purposes.